Drivers and impacts of changes in water quality behavior from the Hermit’s Peak—Calf Canyon wildfire - Tunby, Paige; Van Horn, David J.; González-Pinzón, Ricardo (Frontiers in Water, 2025)
Wildfires significantly alter hydrological and biogeochemical processes, impacting downstream water quality and posing risks to ecosystems and human communities. Following the 2022 Hermit’s Peak-Calf Canyon (HPCC) wildfire in New Mexico, the largest wildfire recorded in the state of New Mexico, we deployed high-resolution in-situ sensors at three locations along a > 160 km fluvial network to investigate event-scale solute transport dynamics and their environmental drivers. Our objective was to evaluate how post-fire runoff events influenced water quality behavior across spatial (headwaters to mid- and high-order streams) and temporal (event to seasonal) gradients. We found that acute water quality impacts were most severe near the burn area, where turbidity reached ~8,500 FNU and dissolved oxygen fell below regulatory thresholds. These extremes, largely missed by traditional discrete sampling, were strongly driven by storm event size and seasonal variability. In contrast, farther downstream, solute export behavior was better predicted by longer-term indicators such as time since the fire and vegetation recovery metrics. Our analysis reveals distinct spatial shifts in concentration-discharge behavior that depend on the water quality parameter type, event features, and site position in the watershed. These findings highlight the need for longitudinal, high-frequency monitoring to detect and anticipate wildfire-induced water quality risks and inform more adaptive, spatially targeted watershed management strategies.